Point mutations in the squalene epoxidase erg1 and sterol 14‐α demethylase erg11 gene of T indotineae isolates indicate that the resistant mutant strains evolved independently - Anke Burmester; Uta‐Christina Hipler; Peter Elsner; Cornelia Wiegand (2021)
The T indotineae population shows a high amount of terbinafine resistant isolates based on different point mutations of squalene epoxidase erg1 (ergosterol) gene. A significant proportion of these isolates also show azole resistance.Elucidation of the molecular mechanism for azole resistance, especially the identification of mutations in the sterol 14-α demethylase Erg11 genes, which encode for enzymes interacting with azoles.Sequencing of putative Erg11 genes and analysis of phenotypic resistance pattern using a microplate-laser-nephelometry-based growth assay.Four different types of Erg11B mutants were detected; two double mutants with Ala230Thr/Asp441Gly, respectively, Ala230/Tyr444His and single mutants with Gly443Glu, Tyr444Cys and Tyr444His. All isolates featured the wild type genotype of Erg11A. All strains demonstrated different combinations of Erg1 and Erg11 genotypes.Resistance against terbinafine and azoles developed several times independently within the T indotineae population. The challenge for fungal treatment is, therefore, that species identification is not enough for prediction of therapeutic efficacy of antifungals. In the future, it will also become important to analyse genes involved in resistance mechanisms.